The ASAP study: association of atherosclerosis with pathobiology in a caucasian cohort—a study of 3400 autopsy reports - Andrea Emese Jakab; Mátyás Bukva; Zoltán Maróti; Tibor Kalmár; István Raskó; Éva Margit Kereszty; Viola Zsuzsanna Papp; Csaba Bereczki (Scientific Reports)
Abstract Cardiovascular plaques result from atherosclerosis. Autopsy investigations of unnatural deaths provide atherosclerosis research. A Central European cohort was studied in a cross-sectional study to determine the origin of atherosclerosis and the link between arterial status and pathobiological variables. This study incorporated 3400 autopsy reports (n = 2318 men; aged 0─96 years; 1928─2010) of persons who died by unnatural causes (suicide, homicide, accident). Age, sex, BMI, abdominal fat thickness, and arterial status of six vascular areas were gathered. The arterial state was divided into five subgroups according to its status. BMI declined from 22.82 kg/m2 in 1931 to 18.43 kg/m2 in 1947, then increased to 27.88 kg/m2 in 2005. Atherosclerotic degeneration begins in the abdominal aorta, then the thoracic, coronary, carotid, ascending, and cerebral arteries. All blood arteries deteriorated faster in men than women until 55. Abdominal aorta damage was the fastest in both sexes. Age is the biggest predictor of atherosclerosis, followed by sex, overweight, and abdominal thickness, according to logistic regression. This is the largest Central European autopsy investigation of six vascular areas. Both sexes develop atherosclerosis in the abdominal aorta in the first decade of life. Being overweight increases the risk. The findings of this study aid healthcare providers in personalized therapy.